2017
DOI: 10.17245/jdapm.2017.17.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Double versus single cartridge of 4% articaine infiltration into the retro-molar area for lower third molar surgery

Abstract: BackgroundThere are no studies regarding 4% articaine infiltration injection into the retro-molar area for an impacted lower third molar (LITM) surgery. This study aimed to evaluate the efficacy of infiltration using 1.7 ml (single cartridge: SC) of 4% articaine versus 3.4 ml (double cartridges: DC) of 4% articaine with 1:100,000 epinephrine in LITM surgery.MethodThis study involved 30 healthy patients with symmetrical LITM. The patients were assigned to receive either a DC or SC of 4% articaine with 1:100,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
3
1
2
Order By: Relevance
“…34 Three studies reported that the dosage of anesthesia could affect the efficiency of anesthesia, in that a greater volume could increase anesthetic efficiency. [28][29][30] This is because a higher volume of the anesthetic agent may yield a higher concentration of the anesthetic agent in the pterygomandibular space. 29 Moreover, Al-Shayyab et al 35 found that many factors could affect the onset time and duration of action of local anesthesia, such as age, gender, and smoking status.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Three studies reported that the dosage of anesthesia could affect the efficiency of anesthesia, in that a greater volume could increase anesthetic efficiency. [28][29][30] This is because a higher volume of the anesthetic agent may yield a higher concentration of the anesthetic agent in the pterygomandibular space. 29 Moreover, Al-Shayyab et al 35 found that many factors could affect the onset time and duration of action of local anesthesia, such as age, gender, and smoking status.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] The pooled outcomes for SOA showed that articaine resulted in shorter SOA than lidocaine, as shown in Figure 4A (SMD, 1.20; 95% CI, 0.50 to 1.89; P = .0007), but with high total heterogeneity (I 2 = 94%, P < .00001) and high heterogeneity for the 2L100 subgroup (I 2 = 95%, P < .00001), so we conducted a sensitivity analysis and found no obvious heterogeneity to change. According to the findings of 3 studies, [28][29][30] we knew a greater dosage could cause more anesthesia efficiency for lidocaine and articaine in LTME. Thus, the dosage used was likely the main cause of the remaining heterogeneity.…”
Section: Subjective and Objective Onset Time Of Anesthesiamentioning
confidence: 99%
“…Their results showed an 83.3% success rate in the 3.4ml group, which had a longer soft-tissue anesthesia interval and less intraoperative pain, and a 53.3% success rate in the 1.7 ml group. In the conclusion of this study, the researchers suggested that infiltration using 3.4 ml of 4% articaine in the retromolar region can be an effective alternative practice for MTMS [12].…”
Section: Introductionmentioning
confidence: 79%
“…A maioria dos estudos utiliza a escala visual analógica (EVA) ou do inglês Visual Analogic Scale (VAS) como meio de avaliação para a resposta dolorosa, falha na anestesia, índice de sucesso, satisfação do paciente e desempenho analgésico. Neste método o paciente passa a ser indiretamente o avaliador do desempenho anestésico (Costa et al, 2005 (Singla et al, 2014) e outro estudo que relata o contrário, onde chegaram a conclusão que utilizando dois tubetes de solução aumenta a taxa de sucesso, tem uma maior duração da anestesia e menos dor durante procedimento cirúrgico (Sawang et al, 2017). Com relação aos efeitos adversos, há relatos na literatura de alguns efeitos após o uso da articaína, como neuropatias envolvendo lábios e línguas (Miller & Lennon, 2000), parestesias e hiperestesias (Malamed et al, 2005), como também a contra-indicação do uso para pacientes com alergia aos antimicrobianos derivados da sulfa e aos sulfitos (Wohrl et al, 2006).…”
Section: Discussionunclassified